2010
DOI: 10.1186/1471-2180-10-216
|View full text |Cite
|
Sign up to set email alerts
|

Identification, expression and serological evaluation of the recombinant ATP synthase beta subunit of Mycoplasma pneumoniae

Abstract: BackgroundMycoplasma pneumoniae is responsible for acute respiratory tract infections (RTIs) common in children and young adults. As M. pneumoniae is innately resistant to β-lactams antibiotics usually given as the first-line treatment for RTIs, specific and early diagnosis is important in order to select the right treatment. Serology is the most used diagnostic method for M. pneumoniae infections.ResultsIn this study, we identified the M. pneumoniae ATP synthase beta subunit (AtpD) by serologic proteome analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Using proteome analysis, PDHB was identified as an antigen that reacts with M. pneumoniae-positive patient sera (Nuyttens et al, 2010). The interaction of PDHB with plasminogen and the previously described binding to human fibronectin (Dallo et al, 2002) show that this molecule belongs to the group of proteins mediating contact to more than one ECM component, such as enolase of P. brasiliensis (Donofrio et al, 2009;Nogueira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Using proteome analysis, PDHB was identified as an antigen that reacts with M. pneumoniae-positive patient sera (Nuyttens et al, 2010). The interaction of PDHB with plasminogen and the previously described binding to human fibronectin (Dallo et al, 2002) show that this molecule belongs to the group of proteins mediating contact to more than one ECM component, such as enolase of P. brasiliensis (Donofrio et al, 2009;Nogueira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…An initial pilot study indicated that vaccination of BALB/c mice with LAMPs resulted in VED after challenge with virulent Mp. We performed proteomic analysis to reveal lipoproteins, elongation factors, chaperones and chaperonins, and cytadherence proteins (previously found to induce strong antibody responses [15][16][17] ) as the most abundant immunogenic and antigenic components of the LAMP fraction ( Fig. 1a-f).…”
Section: Resultsmentioning
confidence: 99%
“…Nuyttens et al . () identified the M. pneumoniae ATP synthase beta‐subunit (AtpD) by serologic proteome analysis, and their results suggest that AtpD can be used as an antigen for the immunodiagnosis of early and acute M. pneumoniae infection in association with adhesin P1. The above research indicated P1 proteins as a promising specific antigen candidate for the diagnosis of M. pneumoniae infection.…”
Section: Discussionmentioning
confidence: 99%
“…Nuyttens et al . () reported the sensitivity and specificity of the C‐terminal part of P1 protein were 69 and 90%, respectively, when tested for IgG antibodies in 54 patients and 86 controls (Nuyttens et al ., ). In our study, two epitopes were used for serodiagnosis, with rP1‐513 having a higher sensitivity than rP1‐534 for IgG and IgM antibodies.…”
Section: Discussionmentioning
confidence: 99%